The Use of Wordwall as a Learning Medium in Indonesian Language Instruction to Improve the Activeness and Learning Outcomes of Fifth-Grade Elementary School Students - Ni Kadek Sutami Yanti; Ni Nyoman Kurnia Wati; Ni Komang Ayu Citta Arsani (IJOEM: Indonesian Journal of E-learning and Multimedia, 2026)
Background: Indonesian language learning at the elementary school level often encounters challenges related to low student activeness and suboptimal learning outcomes due to the dominance of conventional, teacher-centered instructional methods. The integration of digital learning media is considered a potential solution to create a more engaging and interactive learning environment.Aims: This study aims to improve students’ learning activeness and learning outcomes in Indonesian language instruction through the utilization of Wordwall as an interactive digital learning medium for fifth-grade elementary school students.Method: This research employed a Classroom Action Research (CAR) design based on the Kemmis and McTaggart model, conducted in two cycles consisting of planning, action, observation, and reflection stages. The research subjects were 32 fifth-grade students at SD Saraswati Tabanan. Data were collected through observation sheets, learning achievement tests, interviews, and documentation. Qualitative data were used to describe students’ activeness, whereas quantitative data measured improvements in learning outcomes.Results: The results showed a significant improvement in both students’ activeness and learning outcomes. Students’ activeness increased from 60% in the pre-cycle stage to 75% in Cycle I and reached 88% in Cycle II. Meanwhile, the average learning outcome improved from 65.0 in the pre-cycle to 74.3 in Cycle I and increased to 83.5 in Cycle II. Classical mastery also increased from 36.6% to 93%.Conclusion: The use of Wordwall media effectively enhances students’ activeness and learning outcomes in Indonesian language learning. Wordwall creates an interactive, enjoyable, and student-centered learning environment, making it a relevant and effective digital learning innovation for elementary school education.